Entre propostas e reformas: trajetórias e disputas na organização curricular do ensino de História (1971-1987) - Martins, Cinthia Cristina de Oliveira (2016)
The history teaching has established itself as an important subject of debate and academic productions related to graduate and postgraduate programs in the areas of Education and History. However, this disseminated history teaching in elementary schools throughout the second decade of this century is the result of discussions and choices made in the early years of the 1970s and 1980s. For this, we affirm that to critically know the school education currently produced we should first understand the same development process. This argumentative paper presents the teaching of history at the peak of the brazilian civil/military dictatorship (beginning of the 1970s) emphasizing the importance of Social Studies and Moral and Civic Education contents for the organization of teaching from the ideological precepts of government. It shows the historicity of Social Studies and the extent to which the Novista-school project approaches and distanced itself from the model applied during the military government. We propose some curricular changes for teaching in the 1st, 2nd and 3rd levels, highlighting the intentions behind these. At this juncture of educational change proposals we present some organization forms of the teaching category in favor of resisting the educational and labor losses that result from these deployment. And at that moment we emphasize the importance of History Teachers Association (ANPUH) in organizing forms of resistance and combat of the proposed changes. Reaching the transition from the civil-military to civilian regime, in the mid-1980s, knowing the proposal for curriculum reform of the history education in the São Paulo educational system, we discuss the press influence as representative of the converging interests of a society and government conservative segment, in disqualifying the proposal produced by teachers of 1st and 2nd levels, which composed the technical history staff. The convergence of this debate results in understanding how the school curriculum consists of a major field of ideological disputes between government, teachers and society.